The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1962
DOI: 10.1016/0022-3697(62)90248-2
|View full text |Cite
|
Sign up to set email alerts
|

Proton conductivity in borax, Na2[B4O5(OH)4]-8H2O

Abstract: A b stract-Proton conductivity is established by solid State electrolysis experiments on borax powder. T here is m arked anisotropy in electrical conductivity, the 6-axis-direction of a single crystal being the m ost favourable one for protonic conduction. A m inim um tem perature (~ 21 °C) is observed, below which proton conduction ceases. T his effect is discussed in relation to the competition between the reorientation rate of protons and their concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Onoda and De Bruyn (12) studied the system Fe2OJH20 and showed that a very fast surface reaction was followed by a slow diffusion of protons into a goethitelike interphase separating the bulk oxide from the solution. Proton conductivity in borax was studied by Maricic et al (13) who observed that protonic conduction ceases below 21~ Schwabe (14) measured the release of tritium from alumina films, grown in tritiated solution, when an anodic bias was applied after transfer of the specimen to a nontracer solution. Krembs (15) published similar work on Ta205.…”
Section: New Work Since 1959mentioning
confidence: 99%
“…Onoda and De Bruyn (12) studied the system Fe2OJH20 and showed that a very fast surface reaction was followed by a slow diffusion of protons into a goethitelike interphase separating the bulk oxide from the solution. Proton conductivity in borax was studied by Maricic et al (13) who observed that protonic conduction ceases below 21~ Schwabe (14) measured the release of tritium from alumina films, grown in tritiated solution, when an anodic bias was applied after transfer of the specimen to a nontracer solution. Krembs (15) published similar work on Ta205.…”
Section: New Work Since 1959mentioning
confidence: 99%
“…Each of these chains is neighboured by four channels of Na + ions. There are also hydrogen bonds along the b direction between the anionic part of the structure and the water molecules in the cationic channels, d.c. measurements reveal the absolute value of the conductivity along the b axis as three orders of magnitude larger than for that along the sin/~ and c directions [6]. A minimum temperature (,-~ 21°C) is observed below which proton conduction ceases.…”
Section: Inorganic Materialsmentioning
confidence: 97%
“…conduction measurements on proton conductors are frequently reported in the literature [5,6,8,11,39]. Generally, the conductivity is calculated from the voltage over and the current through the sample.…”
Section: DC Conduction Measurementsmentioning
confidence: 99%
“…Mechanisms involving such proton jump/Grotthuss mechanism was proposed for ice by N. Bjerrum a long time ago [234,235] and is consistent with oxygen and deuteron/tritium diffusion coefficients measured in compounds like H 3 OClO 4 [53] and in many other hydrates. [269][270][271][272][273] sublattice is also used, as for Ag + , Na + , etc. superionic conductors.…”
Section: Proton Transfer Mechanismsmentioning
confidence: 99%